Manejo das plantas daninhas no milho irrigado por meio da integração capinas e consorciação com gliricídia - Tavella, Leonardo Barreto (2014)
The objective of this work was to verify the effects of the combination between weeds and intercropping with gliricídia (thirty viable seeds m-2 broadcast) on the weed and corn yields. Completely randomized blocks design with four repetitions in subdivided parts was used. Hybrids (AG 1051 e BR 205) were cultivated in the parcels, and in the subportions the following treatments were applied: two weeds (twenty and forty days after corn sowing); a weed accomplishing 20 days after corn sowing + gliricídia sowing after weed; gliricídia sowing on the occasion of the corn sowing + weed accomplishing forty days after corn sowing; gliricídia sowing on the occasion of corn sowing; without weed. There was among hybrids with respect to baby corn, green spike and grains. The greatest yields were obtained through the treatment with two weeds, but the execution of a weed 20 days after corn sowing + gliricídia sowing after weed did not differ with respect to the yield of these three products according the weeds. Gliricídia sowing on the occasion of the sowing corn + weed after did not differ from the weeds with respect to the green spikes yield. Gliricídia sowing on the occasion of the corn sowing allowed averages superior to the treatment without weed and in some growth character and corn yield. Therefore, gliricídia controlled weed partially and its combination with weed has benefits